Regulation of glucose metabolism by MuRF1 and treatment of myopathy in diabetic mice with small molecules targeting MuRF1 - Labeit, Siegfried; Hirner, Stephanie; Bogomolovas, Julijus; Cruz, André; Myrzabekova, Moldir; Moriscot, Anselmo; Bowen, Thomas Scott; Adams, Volker (International journal of molecular sciences, 2021)
The muscle-specific ubiquitin ligase MuRF1 regulates muscle catabolism during chronic wasting states, although its roles in general metabolism are less-studied. Here, we metabolically profiled MuRF1-deficient knockout mice. We also included knockout mice for MuRF2 as its closely related gene homolog. MuRF1 and MuRF2-KO (knockout) mice have elevated serum glucose, elevated triglycerides, and reduced glucose tolerance. In addition, MuRF2-KO mice have a reduced tolerance to a fat-rich diet. Western blot and enzymatic studies on MuRF1-KO skeletal muscle showed perturbed FoxO-Akt signaling, elevated Akt-Ser-473 activation, and downregulated oxidative mitochondrial metabolism, indicating potential mechanisms for MuRF1,2-dependent glucose and fat metabolism regulation. Consistent with this, the adenoviral re-expression of MuRF1 in KO mice normalized Akt-Ser-473, serum glucose, and triglycerides. Finally, we tested the MuRF1/2 inhibitors MyoMed-205 and MyoMed-946 in a mouse model for type 2 diabetes mellitus (T2DM). After 28 days of treatment, T2DM mice developed progressive muscle weakness detected by wire hang tests, but this was attenuated by the MyoMed-205 treatment. While MyoMed-205 and MyoMed-946 had no significant effects on serum glucose, they did normalize the lymphocyte-granulocyte counts in diabetic sera as indicators of the immune response. Thus, small molecules directed to MuRF1 may be useful in attenuating skeletal muscle strength loss in T2DM conditions.
Gesehen am 03.05.2021